Some Previously Relevant Aspects of Academic Life: Venia Legendi and the Status of a Private Docent at the University of Latvia (1919–1944) - Baltiņš, Māris (History of Engineering Sciences and Institutions of Higher Education, 2022)
The article presents the results of the research on venia legendi (the right to deliver lectures at the university) and the status of private docent at the University of Latvia (UL) until 1944. The term «private docent» was used worldwide in the 18th century; it is still in use in Germany, Austria and Switzerland. In Latvia, it was introduced in the 1860s at the first higher education institution established in the current territory of Latvia – Riga Polytechnicum. The terms «private docent» and «venia legendi» were used in Latvia until the end of World War II. In the present study, the author explains how these terms were used at the UL during the interwar period and during World War II considering the empirical data obtained in the course of research of archival documents and library collections. The article provides an overview of the private docents working at the UL from 1919 to 1944 and their activities in this period.